Face to face communication as marketing strategy: a case in "NASAD (M) Sdn Bhd" / Nor Liyana Syaifudin - Syaifudin, Nor Liyana (2017)
Nowadays, in a growing business there have communication technology that had changed the face to face communication strategy to media communication strategy such as television, social network, advertising and so on. Communication is important in order to deliver information to other person. If the information is not clear it will affect the conflict because of misunderstanding. The title of this study is "Face to Face Communication as Marketing Strategy: A Case in Nasad (M) Sdn Bhd". The first purpose of this study is to determine elements in face to face communication as marketing strategy in Nasad (M) Sdn Bhd and the second purpose is to identify the dominant element influences in a good face to face communication. The results of the research will discovered the most important element in face to face communication for charity purpose to gain fundraising that company must focus.